Gambaran Tingkat Kepuasan Pasien BPJS Rawat Jalan Terhadap Pelayanan Kefarmasian Di Rumah Sakit "X" di Sidoarjo - Andri Priyoherianto; Merry Patrilinilla Chresna; Panji Ratih Suci; Nafila Amelia Putri; Luluk Sunarti (Calory Journal Medical Laboratory Journal, 2024)
Pharmaceutical service is direct and responsible service to patients related to pharmaceutical preparations to improve the quality of life of the patients. One of the health service facilities is the hospital. Hospitals are required to provide quality services for the creation of a satisfaction. Satisfaction is closely related to the expected service and the reality of service that has been given. Therefore it is necessary to measure patient satisfaction to see how far the services provided in accordance with the expectations of patients. The research is using deskriptif prospektif metode and using purposive sampling technique. The study was conducted in February 2020, by giving a questionnaire to the visiting patients and having receivedpharmaceutical services at the "x" hospital in Sidoarjo. Able to communicated well, used Indonesian, willing to be interviewed with the provisions of 18 years old, 19-45 years old and ≥46 years old. The perception of patients satisfied about the tangible of 72%, emphaty indicator of 66% with satisfied categories, and reability indicator of 67% with satisfied categories so the average percentage of overall out patient BPJS satisfaied. The conclusion of this research is that the services provided in the installation of the "x" pharmacy to patients are categorized as well.